Co-catalytic mechanism of Au and Ag in silicon etching to fabricate novel nanostructures. Issue 117 (9th November 2015) - Li, Ruike; Li, Meicheng; Li, Yingfeng; Fu, Pengfei; Luo, Younan; Huang, Rui; Song, Dandan; Mbengue, Joseph Michel
Abstract : The co-catalytic mechanism of silicon etching with a bilayer Au and Ag nanofilm is revealed, resulting in two very different structures. Abstract : Metal-assisted chemical etching is a very popular method of fabricating silicon nanostructures. For the dissolution and recrystallization of Ag and the inertia of Au, we present a co-catalytic mechanism of silicon etching using non-overlapping Au and Ag nanofilms. Meanwhile, two kinds of novel nanostructures are obtained by changing the relative positions of the two nanofilms. The results show that regardless of whether the Ag or Au nanofilm is the upper layer, the Ag nanofilm will first react to etch the silicon substrate into silicon nanowires (Si NWs). Afterwards, the Au nanofilm will re-etch the Si NWs into thick pillars (Ag upper) or ultrathin porous Si NWs (Au upper). It should be noted that the vertical etching rates of the two layers are not observably different, in contrast to when the Au and Ag nanofilms are used separately, in which the vertical etching rate of the Ag nanofilm is much higher than that of the Au nanofilm. This occurs because the subsequent re-etching process by the Au nanofilm is conducted at multiple surfaces because Au can generate excessive holes during the decomposition of hydrogen peroxide. Furthermore, this study presents a feasible method for the fabrication of individual, thick (∼200 nm) silicon pillars and ultrathin (∼25 nm) porous Si NWs. These insights are significant for the syntheses of many nanostructures.